LETTURA ESTENSIVA E ALCUNI SUGGERIMENTI NELL’INSEGNAMENTO DI ITALIANO (Journal of Foreign Language Studies, 2023)
Reading is a skill that facilitates learner’s language acquisition. Most learners of foreign language often have the habit of reading intensively in order to answer questions or to solve tasks and exercises that accompany the texts. Extensive reading, however, is a method of reading for pleasure with the aim of encouraging learners in general and those of foreign languages in particular to improve their reading skills, enrich their vocabulary and widen their knowledge. This study, using synthetic and analytic methods, presents the benefits of extensive reading and provides some suggestions for teaching practices.
Keywords: reading skil; extensive reading; reading habit